Analisis Faktor Yang Mempengaruhi Masyarakat Terhadap Pembelian Makanan Secara Online - Lutfi, Lutfi Alawiyah; Utami, Suci Nur; Listyanto, M. Erwin Dwi (Journal of Agribusiness, Social and Economic, 2024)
The current development of e-commerce in Indonesia cannot be separated from people's habits that demand practicality and speed. There has been a change in consumer behavior from usually buying food offline to now switching to buying food online using services in the marketplace. This has led to an increase in food delivery transactions. The purpose of this research is to determine the factors that influence consumer behavior in consumer purchasing decisions in purchasing food using online delivery services. The sampling method used by the author is comfortable sampling, namely a sampling technique using free samples according to the author's wishes. The sample size is 100 respondents. The research results show that overall the factors have a significant influence and simultaneous contribution. And partially, the factor that has a significant influence is the personal control factor, while the attitude and subjective norm factors do not have a significant influence on online food purchasing decisions.